Study of the shape and angularity of abrasive particles, vegetable and mineral, to be incorporated into solid soap with exfoliating action: Kaolin, bentonite, rice microspheres, bamboo and apricot seed - Gonçalves , Jumara Aparecida Batista; Pinheiro , Gilmar de Oliveira; Diaz , Francisco Rolando Valenzuela (Seven Editora, 2023)
This research work presents a contribution to the areas of cosmetology and materials, focused on the use of natural products as exfoliating agents in solid soap.It consists of a literature review on the use of different exfoliating agents in cosmetics, a field survey to demonstrate the availability of these products in commercial stores, and tests to characterize their abrasive particles.The characterization in terms of shape and angularity of the abrasive particles of the selected exfoliating agents, was obtained through the Scanning Electron Microscopy-SEM tests, using the Scanning Electron Microscope - FEI Inspect 50™, of Particle Size and Shape Distribution.This research work consists of presenting the analysis of images of exfoliating agents, obtained through different methods, with the objective of classifying them according to their shape and angularity, which is one of the characteristics to be considered in an abrasive particle.The results obtained were in agreement with the literature in terms of shape and angularity, normally found in abrasive particles, as well as satisfactorily demonstrating the hypothesis of the use of kaolin, bentonite, rice microspheres, bamboo and apricot seed as exfoliating agents to be incorporated into solid soaps, motivating the expansion of research regarding the observation of their performance,  but in this case with a tribological look on the subject. DOI:https://doi.org/10.56238/alookdevelopv1-150